Exploring the search trends: Inter Milan's triumph in Indonesia - Laksana, Eko Pramudya; Fajaruddin, Syarief; Andi, Tri; Hudha, Muhammad Nur (Research and Social Study Institute, 2024)
This article explores the popularity of Inter Milan in Indonesia through an in-depth analysis of Google search trends. Data from Google Trends between May 2023 and May 2024 was collected and analyzed using a rigorous qualitative methodology with an ethnographic approach. The study focuses on two main metrics: interest over time and regional distribution per province. The results show Inter Milan's search volume and regional interest fluctuate, with a notable peak during the UEFA Champions League final against Manchester City on June 11, 2023. The research illuminates the multifaceted and enthusiastic fan base of Inter Milan and the club's dedication to social initiatives and community engagement.